2021
DOI: 10.1007/s10854-021-05871-0
|View full text |Cite
|
Sign up to set email alerts
|

The tungsten oxide within phosphate glasses to investigate the structural, optical, and shielding properties variations

Abstract: We prepared a series of sodium phosphate glasses by changing WO3/P2O5 content and investigated structure optical and radiation shielding features as a function of glass composition. The average density (⍴ ) and was found to increase gradually from 2.49 to 3.07 g/cm 3 while the average molar volume values reduced from 47.37 to 44.28 cm 3 /mol with WO3 addition. Also, the average field strength was also computed and found to increase with increasing WO3. The study of optical absorption spectra reveals that, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 31 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The shielding capability of improved materials is positively connected with larger values of Z eff . This suggests that a greater number of gamma rays experience attenuation while passing through materials characterized by higher Z eff values [41]. The results, taken from Figure 14, also showed that adding cadmium at the expense of aluminum led to an increase in Z eff values in different energy values from 0.001 to 15 MeV.…”
Section: Gamma Shielding Studymentioning
confidence: 77%
See 1 more Smart Citation
“…The shielding capability of improved materials is positively connected with larger values of Z eff . This suggests that a greater number of gamma rays experience attenuation while passing through materials characterized by higher Z eff values [41]. The results, taken from Figure 14, also showed that adding cadmium at the expense of aluminum led to an increase in Z eff values in different energy values from 0.001 to 15 MeV.…”
Section: Gamma Shielding Studymentioning
confidence: 77%
“…This phenomenon can be explained by the fact that at low energy levels a glass of small thickness is required, which is re ected in the low HVL values attributed to the photoelectric processes [40]. However, in the medium and high energy ranges, this requires materials with a higher thickness in order to reduce the penetration of gamma rays into the prepared materials and thus reduce health damage [41]. It is noted also from Figure 12 that replacing aluminum with cadmium reduces HVL values.…”
Section: Gamma Shielding Studymentioning
confidence: 99%
“…Furthermore, the MFP refers to the average distance between two consecutive photon interactions with the absorber material. MFP is used as an additional criterion for assessing the ability of a specific material to shield against radiation and it can be obtained as the following [54]: In addition, Z eff measures how well a particular martial protects against ionizing radiation. Materials with higher Z eff values have greater effectiveness in attenuating ionizing radiation [54].…”
Section: Radiation Shieldingmentioning
confidence: 99%
“…All of the Zn 0.9 Ni 0.1 Co 2-x Fe x O 4 samples showed consistent patterns in the MFP values as a function of the incident photon energy.In addition, Z eff measures how well a particular martial protects against ionizing radiation. Materials with higher Z eff values have greater effectiveness in attenuating ionizing radiation[54].Figure9illustrates the changes in Z eff values as a function of incident photon energy for Zn 0.9 Ni 0.1 Co 2-x Fe x O 4 samples. According to the graph, Z eff reaches its highest values at low photon energy.…”
mentioning
confidence: 98%
“…On the other hand, in the glasses absorption spectrum, it is noticed that the incident wavelengths decrease as absorbance rises rapidly, producing the fundamental absorption edge (UV 'cut off'). Optical band gap (E g ) can be determined through the optically induced transition process in which photon energy is larger than the energy difference between VB and CB of the material [32][33][34]. Determining this energy in glass materials provides information regards the structural modification and chemical bond nature.…”
Section: Absorption In First Region (Uv Region) and Optical Band Gapmentioning
confidence: 99%